Reducing Staphylococcus aureus growth on Ti alloy nanostructured surfaces through the addition of Sn. Issue 12 (19th June 2015) - Verissimo, Nathália C.; Geilich, Benjamin M.; Oliveira, Haroldo G.; Caram, Rubens; Webster, Thomas J.
Abstract: β‐type Ti alloys containing Nb are exciting materials for numerous orthopedic and dental applications due to their exceptional mechanical properties. To improve their cytocompatibility properties (such as increasing bone growth and decreasing infection), the surfaces of such materials can be optimized by adding elements and/or nanotexturing through anodization. Because of the increasing prevalence of orthopedic implant infections, the objective of this in vitro study was to add Sn and create unique nanoscale surface features on β‐type Ti alloys. Nanotubes and nanofeatures on Ti‐35Nb and Ti‐35Nb‐4Sn alloys were created by anodization in a HF‐based electrolyte and then heat treated in a furnace to promote amorphous structures and phases such as anatase, a mixture of anatase‐rutile, and rutile. Samples were characterized by SEM, which indicated different morphologies dependent on the oxide content and method of modification. XPS experiments identified the oxide content which resulted in a phase transformation in the oxide layer formed onto Ti‐35Nb and Ti‐35Nb‐4Sn alloys. Most importantly, regardless of the resulting nanostructures (nanotubes or nanofeatures) and crystalline phase, this study showed for the first time that adding Sn to β‐type Ti alloys strongly decreased the adhesion of Staphylococcus aureus ( S. aureus ; a bacteria which commonly infects orthopedic implants leading to their failure). Thus, this study demonstrated that β‐type Ti alloys with Nb and Sn have great promise to improve numerous orthopedic applications where infection may be a concern. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3757–3763, 2015.